Pengembangan Sistem Survei Kepuasan Pengunjung pada UPT P2BJ Jawa Timur dengan Metode SERVQUAL dan Analisis Importance & Performance Matrix - Ardyani Nalendri Styadi; Ismiarta Aknuranda; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Currently, public satisfaction survey activities conducted by UPT P2BJ Provinsi Jawa Timur are undertaken by survey consultants from external organizations. Survey consultants visited UPT P2BJ visitors's place and distributed questionnaires manually so the survey required a complicated effort. Therefore, UPT P2BJ would like to conduct the survey within the internal organization but they hope the survey doesn't interfere the main business process of them. Not only that, the results of the current survey only grouped the questionnaire components into two groups: satisfied and dissatisfied. The use of a combination of SERVQUAL and IPA methods is expected to provide more specific analysis results on each component of the survey so the results can be a more appropriate guide in decision making process. Therefore, this research will develop visitor satisfaction survey system to UPT P2BJ East Java with Service Quality (SERVQUAL) and Importance Performance & Matrix method. The system is expected to automate UPT P2BJ survey activities. The system builds on a waterfall development model that begins the development with business process and requirements analysis, system design, system implementation, and testing. The test results from the implementation of the system show that the system met the functional requirements of users, the system can run on all type and version of web browsers that tested in the SortSite tool, and the system's time efficiency are 50.1% for respondent and 98.9% for administrator.